Evaluasi Pengalaman Pengguna Menggunakan Metode User Experience Questionnaire : Studi Kasus : KLAMPID New Generation - Ardina Sagita Ramadhani; Anita Wulansari; Eristya Maya Safitri (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
This research evaluates the user experience of KLAMPID New Generation, which is a digital service managed by DISPENDUKCAPIL Surabaya City. Evaluation is carried out using the User Experience Questionnaire method to measure the attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty of the application. The analysis result show that this application has a good value and shows positive evaluation on all scales, on the perspicuity scale it has a mean value of 1.69 and benchmark is “above average”, the efficiency scale has a mean value of 1.68 and the benchmark is “good”, the attractiveness scale has a mean values of 1.63 and the benchmark is “good”, the dependability scale has a mean value of 1.50 and the benchmark is “good”, the stimulation scale has a mean value of 1.48 and the benchmark is “good”, and the novelty scale has a mean value of 1.24 and the benchmark is good. This evaluation show that KLAMPID New Generation has been successful in meeting needs and providing a positive user experience. The implication of this research is to sustain strengths and enhance features, ensuring the service remains innovative, user-friendly, and supportive of improved public service delivery.